2023
DOI: 10.1136/bmjoq-2022-002155
|View full text |Cite
|
Sign up to set email alerts
|

Development and acceptance of a new adherence monitoring package to identify non-adherent patients with polypharmacy in primary care: a feasibility study

Abstract: BackgroundAdherence to pharmacotherapy is crucial to prevent symptom deterioration in chronic diseases. However, non-adherence to chronic treatments is prevalent, especially in polypharmacy. Practical tools to assess adherence to polypharmacy in primary care are missing.AimsWe aimed to develop an Adherence Monitoring Package (AMoPac) for general practitioners (GPs) to identify patient non-adherence. We tested the feasibility and acceptance of AMoPac in the primary healthcare setting.MethodsAMoPac was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…AMoPac is a tool to assess, evaluate and report patients’ medication adherence to a healthcare professional. It consists of (1) electronic adherence monitoring, (2) feedback on patients’ intake behaviour given by a pharmacist, (3) analysis of adherence data and (4) adherence report with adherence metrics including clinical-pharmaceutical recommendations to the GP 10 11…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AMoPac is a tool to assess, evaluate and report patients’ medication adherence to a healthcare professional. It consists of (1) electronic adherence monitoring, (2) feedback on patients’ intake behaviour given by a pharmacist, (3) analysis of adherence data and (4) adherence report with adherence metrics including clinical-pharmaceutical recommendations to the GP 10 11…”
Section: Methodsmentioning
confidence: 99%
“…We developed the Adherence Monitoring Package (AMoPac) for monitoring, evaluating and reporting adherence. The feasibility and the acceptance of AMoPac among GPs have previously been assessed in a pilot study among patients with heart failure 10. Although the feasibility and acceptance could be proven in the pilot study, it also revealed technical problems with the integrated transmission of the adherence report into GPs’ electronic health records.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietrich et al, conducted a feasibility study on newly developed adherence monitoring package (AMoPac) to identify non-adherent patients with polypharmacy in primary care, highlighting the strengths and limitations of a multi-assessment approach to adherence with a potential to look deeper into the non-adherent patients (75). AMoPac was developed based on peer-reviewed literature, encompasses three essential elements: (1) electronically tracking patients' medication intake over a four-week period, (2) providing intake behavior feedback via pharmacists, and (3) generating an adherence report intended for communication with general practitioners (GPs).…”
Section: Multi-approach Settingmentioning
confidence: 99%
“…With the utilization of AMoPac, GPs have the option to incorporate an adherence monitoring period prior to making adjustments to the therapy. This enables them to gain insights into non-response and non-adherence issues (75,76). In a multi-approach setting, where non-adherence to medication can be attributed to a diverse range of factors, encompassing both unintentional and intentional aspects, Tab.…”
Section: Multi-approach Settingmentioning
confidence: 99%